Rancang Bangun Mesin Pemipil dan Penghancur Tongkol Jagung - Agil Renaldy; Edy Prabowo; Indra Kusuma; Winarto Winarto (Jurusan Teknologi Pertanian, 2020)
Corn is one of the important plants for human life, especially in Indonesia. This is because corn is the second food crop commodity after rice. In Indonesia, there are still many post-harvest maize product processing using the traditional method by peeling corn by hand, so that the yield of corn production is not comparable with the labor for processing the corn harvest. Agricultural statistics show that maize production in Indonesia has always increased from year to year. In order to better support the conversion process of corn cobs waste into animal feed, a chopper is needed. The machine functions to chop the corn cobs so that they are easier for livestock to consume as well as accelerate the work of bacteria during the fermentation process. If the two processes are carried out on separate machines, it will take a long time to complete. This study aims to make a machine that combines a corn sheller machine with a corn cobs crusher. The results of testing the corncob crusher and shelling machine gave 10 kg/hour shelling capacity, 13% unshipped corn, 68.9% corn shelling yield, 15 kg/hour corn cobs crushing machine capacity, 85.28% yield of corn cobs crushing.